Aseptic Loosening of Total Hip Arthroplasty: Infection Always Should be Ruled Out - Parvizi, Javad (Springer-Verlag, 2011)
BACKGROUND: It is believed that some cases of aseptic failure of THA may be attributable to occult infections. However, it is unclear whether preoperative erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) are more likely elevated in these patients than those without overt infection. QUESTIONS/PURPOSES: We asked whether some patients with aseptic THA failures have abnormal serologic indicators of periprosthetic joint infection (PJI) at the time of revision, namely ESR and/or CRP. METHODS: Three hundred twenty-three revision THAs for aseptic loosening from 2004 to 2007 were retrospectively evaluated. We categorized all cases into two groups: (1) those with overt PJI (n = 14) plus patients who had a positive intraoperative culture during the index revision (n = 13) and (2) those who did not require rerevision (n = 276) or required surgery for noninfected causes (n = 20). Mean and frequency of abnormal ESR and CRP were compared between the two groups. The minimum followup was 11 months (average, 35 months; range, 11-54 months). RESULTS: The mean and frequency of abnormal CRP in first group (n = 27) at 2.1 mg/dL and 48% respectively, were greater than those of the uninfected (n = 296) at 1.2 mg/dL and 27%, respectively. However, there were no differences between two groups regarding mean or frequency of abnormal ESR. CONCLUSION: Some patients with presumed aseptic loosening may have abnormal serologic indicators of PJI that either have escaped diagnosis or were not adequately investigated. All patients undergoing revision THA should have ESR and CRP measured preoperatively and those with abnormal CRP should have additional evaluations to rule out or confirm PJI. LEVEL OF EVIDENCE: Level III, retrospective comparative study. See the Guidelines for Authors for a complete description of levels of evidence.